Implementasi pendidikan pesantren tahfidz dan gerakan budaya qur’ani di Indonesia - Indhra Musthofa; Husnul Khotimah (At Turots: Jurnal Pendidikan Islam, 2023)
The existence of pesantren tahfidz in correlating with Qur'ani culture becomes a supporting factor in forming a generation that instills the value of Qur'ani values. The Tahfidz Islamic Boarding School is an activity within the Islamic Boarding School that prioritizes the process of memorizing the Qur'an accompanied by good and correct teaching of reading the Qur'an. The activities of the Tahfidz Islamic Boarding School include the culture of having to recite the Koran every day, because of the orderly rules that are required to recite the Koran in it. The activities of the Tahfidz pesantren are expected to be a solution in instilling the Qur'anic cultural movement in Indonesia. So that it is embedded in a student with a positive attitude, applying the habit of having to recite the Koran and the habit of practicing Islamic teachings. The purpose of the Qur'anic cultural movement in Indonesia is to ground the Qur'an, the Qur'an has always been the main and first source of Islam, and to create a religious society. The method that the author uses is library research or library research with the data source in the form of writings from previous research related to the theme being discussed. In this article, the author will try to explain about Tahfidz pesantren and the Qur'anic cultural movement in Indonesia